Empowering Teachers to Make Literacy-Based Learning Evaluations - Muhammad Hafidz Khusnadin; Verry Albert Jekson Mardame Silalahi; M. Wildanul Ulum; Imetrimawati Tafonao; Febri Pramudya Wardani (Jurnal Pengabdian Cendekia, 2025)
This study aimed to empower teachers in designing and implementing literacy-based evaluations through a community-engaged professional development program. Responding to the need for improved assessment literacy, the initiative involved workshops and classroom mentoring for in-service teachers in elementary and secondary schools. Using a qualitative descriptive and action-based approach, data were collected through observation sheets and semi-structured interviews, then analyzed thematically. Results indicated a significant shift in teacher practices, from reliance on traditional assessments toward the use of formative, student-centered tools such as rubrics and reflective journals. Teachers demonstrated increased confidence, autonomy, and collaboration, reflecting professional growth and greater assessment literacy. The intervention also fostered reflective thinking and peer support, aligning well with national and international literacy frameworks. Despite challenges such as time limitations and varied readiness among teachers, the program showed that targeted, participatory training can foster sustainable changes in assessment practice. The study recommends integrating such models into broader teacher development policies and highlights the need for future research to explore long-term impacts on both teaching and student outcomes.